Autonomy and dependence: a discussion paper on decision‐making in teenagers and young adults undergoing cancer treatment. (17th April 2015) - Davies, Jane; Kelly, Daniel; Hannigan, Ben
Abstract Aim A discussion which aims to explore the diversity of decision‐making during teenage and young adult cancer treatment. The discussion will be related to the concepts of autonomy, dependence and decision‐making in this age group. Background The experience of cancer involves a significant series of treatment decisions. However, other non‐treatment decisions also have to be made which can relate to any aspect of everyday life. These decisions occur against the backdrop of young people's disease experience. Design Discussion paper. Data sources A literature search for the period 1990–2013 was undertaken. This included searching the following databases: Cumulative Index for Nursing and Allied Health Literature (CINAHL), SCOPUS, Medline, DARE, Applied Social Sciences Index and Abstracts (ASSIA), (Psych Info) and The Cochrane Library. Implications for nursing There is a lack of evidence into the experience of everyday decisions made by young people during cancer treatment. This may affect them in the form of unmet needs that nurses, or other professionals, fail to appreciate. Conclusion Further exploration of how teenagers and young adults experience the range and process of decision‐making during cancer treatment could be useful in helping to provide effective supportive care for this age group.